2011
DOI: 10.1038/ejcn.2011.45
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics affect the clinical inflammatory parameters of experimental gingivitis in humans

Abstract: Objectives: To determine the effects of a probiotic milk drink consumed over a period of 28 days, regarding the expression of clinical inflammatory parameters of the oral gingiva during various phases of plaque-induced gingivitis. Methods: Twenty-eight adults with healthy gingiva took part in a prospective and clinical-controlled study. The test group was advised to consume a probiotic milk drink (Yacult) daily during a period of 4 weeks; the control group did not receive any probiotic food or drink. After 2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 37 publications
5
69
0
3
Order By: Relevance
“…Seven studies found decreased BOP after treatment with probiotic bacteria compared with placebo ( Fig. 12.2 ) Slawik et al 2011 ;Teughels et al 2013 ;Tsubura et al 2009 ;Twetman et al 2009 ;Vicario et al 2013 ;Vivekananda et al 2010 ). However, Teughels et al ( 2013 ) did not fi nd this decrease signifi cant.…”
Section: Gingivitis and Periodontitismentioning
confidence: 96%
See 1 more Smart Citation
“…Seven studies found decreased BOP after treatment with probiotic bacteria compared with placebo ( Fig. 12.2 ) Slawik et al 2011 ;Teughels et al 2013 ;Tsubura et al 2009 ;Twetman et al 2009 ;Vicario et al 2013 ;Vivekananda et al 2010 ). However, Teughels et al ( 2013 ) did not fi nd this decrease signifi cant.…”
Section: Gingivitis and Periodontitismentioning
confidence: 96%
“…However, Iniesta and co-workers ( 2012 ) were not able to confi rm these fi ndings. Three clinical trials have looked upon the effect of probiotics on subjects with experimental gingivitis (Hallström et al 2013 ;Slawik et al 2011 ;Staab et al 2009 ): two with positive and one with a negative outcome (Table 12.2 ).…”
Section: Gingivitis and Periodontitismentioning
confidence: 99%
“…Esses dados sugerem que o agente pode ter efeitos benéficos na inflamação gengival 21 . Em outro estudo, também com doença induzida e empregando a mesma bebida láctea contendo 10 8 UFC, houve melhora no sangramento a sondagem e no volume do fluido do sulco gengival, ambos foram significativamente menores (p<0,005) para o grupo teste (n: 11), cujos membros consumiram a bebida por quatro semanas 22 . Esses resultados sugerem que o consumo diário dessa bebida pode reduzir os efeitos das doenças gengivais induzidas pela placa.…”
Section: Placa E Gengiviteunclassified
“…However, another study reported that the adjunctive use of a probiotic tablet, containing Streptococcus oralis KJ3, Streptococcus uberis KJ2 and Streptococcus rattus JH145, did not significantly improve the therapeutic outcomes of scaling and root planing when compared to the placebo group (235). In subjects with gingivitis, the use of probiotics has shown a positive clinical effect in some studies (236, 237, 238), while Iniesta et al (239) reported decreased levels of P. intermedia in saliva, and P. gingivalis in subgingival plaque, but no improvements in plaque and gingival indexes after probiotic administration. Moreover, in healthy children subjected to complete oral prophylaxes followed by probiotic administration in the form of curd, no differences in gingival health were observed in comparison to the control (240).…”
Section: Introductionmentioning
confidence: 99%